ANALISIS KELAYAKAN OBJEK EKOWISATA AIR TERJUN MANDIN MANGAPAN DI DESA PARAMASAN ATAS KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Khairuddin Khairuddin; Khairun Nisa; Asysyifa Asysyifa (Universitas Lambung Mangkurat, 2020)
Mandin Mangapan Waterfall has an altitude of ± 40 meters is one of the beautiful potential natural that is found in the village of Paramasan Atas, Banjar Regency. The purpose of this study is to analyze the feasibility of Mandin Mangapan Waterfall as an ecotourism object and to get the information of the public perception of the Waterfall of Mandin Mangapan. The respondents in this research are the community of Niwak Village (Dusun Niwak) RT. 04. Interviews with respondents were conducted by using the questionnaires. Total score of the landscape assessment of Mandin Mangapan Falls is about 28, and it was included in the category of Class A (high quality) and the assessment of the potential of tourist attraction of 72.30% indicates that the location of Mandin Mangapan Waterfall is feasible to be developed. Community of Dusun Niwak stated that Waterfall is the most attractive natural potential of 88.90% in that place and 83.33% of the community hope that they could be involved in ecotourism development plan that will have a direct impact on the economy of the community in that area.Keywords: feasibility analysis. ecotourism, Mandin Mangapan Waterfall